Biological Treatment of Solid Waste 2015
DOI: 10.1201/b18872-15
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Diversity of Vermicompost Bacteria that Exhibit Useful Agricultural Traits and Waste Management Potential

Abstract: In the present work, experimentation was carried out to study the behavior of exhausted grape marc during the bio-drying process. This process was chosen as an alternative to the typical grape marc thermal drying approach. The aim was to reduce the moisture level thanks to the biological exothermal reactions, and to increase the energy content in the biodried grape marc. The target was the generation of a product interesting for energy options. For the development of the research, a biological pilot reactor an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…For example, research has reported the disease-suppressive properties of thermophilic compost and vermicompost on a wide range of phytopathogens, including Rhizoctonia, Phytophthora, Plasmidiophora brassicae, Gaeumannomyces graminis, and Fusarium species. Bio-composts have also proven effective in controlling arthropods and nematodes, improving overall soil health [42,44].…”
Section: Biocontrol Of Pathogenic Microorganisms In the Soil With Com...mentioning
confidence: 99%
“…For example, research has reported the disease-suppressive properties of thermophilic compost and vermicompost on a wide range of phytopathogens, including Rhizoctonia, Phytophthora, Plasmidiophora brassicae, Gaeumannomyces graminis, and Fusarium species. Bio-composts have also proven effective in controlling arthropods and nematodes, improving overall soil health [42,44].…”
Section: Biocontrol Of Pathogenic Microorganisms In the Soil With Com...mentioning
confidence: 99%
“…The interesting technologies of recent years are Mechanical Biological Treatment (MBT) and Biological Mechanical Treatment (BMT). Biodrying (Biological Drying) where solid wastes are readily bio compatible biologicalmechanical [2].…”
Section: Introductionmentioning
confidence: 99%
“…The results of processing using biodiesel can serve as fuel substitute fuel (RDF) which is fuel produced from various types of waste such as waste, industrial waste or commercial waste. RDF can be used as a coal substitute [2]. The most obvious uses of the bio drying process are the decrease in odor, volume, and weight of waste, which can improve dental, transport and solid waste disposal at the time of large solid waste volumes.…”
Section: Introductionmentioning
confidence: 99%